2023
DOI: 10.3390/antibiotics12010161
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Biomarkers in Influenza and COVID-19 Community-Acquired Pneumonia in Adults

Abstract: Pneumonia is a growing problem worldwide and remains an important cause of morbidity, hospitalizations, intensive care unit admission and mortality. Viruses are the causative agents in almost a fourth of cases of community-acquired pneumonia (CAP) in adults, with an important representation of influenza virus and SARS-CoV-2 pneumonia. Moreover, mixed viral and bacterial pneumonia is common and a risk factor for severity of disease. It is critical for clinicians the early identification of the pathogen causing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…is, though, not an issue. Multiple reports indicate that each of these viruses can cause severe illness in patients presenting to the hospital with CAP [ 27 , 28 ]. Moreover, in the articles reviewed above, the definitions of HAP and VAP necessitated that the patient meets standard clinical and radiographic criteria for new pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…is, though, not an issue. Multiple reports indicate that each of these viruses can cause severe illness in patients presenting to the hospital with CAP [ 27 , 28 ]. Moreover, in the articles reviewed above, the definitions of HAP and VAP necessitated that the patient meets standard clinical and radiographic criteria for new pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…ARDS in patients with COVID-19 can also increase the levels of this marker, as well as clinical conditions of biliary pancretitis, fungal infections, lung carcinoma, among others. However, although PCT is not a reliable marker of the presence of bacterial co-infection, its dosage of up to 0.25 ng/mL is indicative of its absence and is an aid to avoid inappropriate treatment with antibiotics in patients infected with SARS-CoV-2 [38,[41][42][43]. Among the advantages of using procalcitonin as an inflammatory marker, it can be also considered the absence of interference of its levels with the use of corticosteroids, rapid elevation after induction, high sensitivity, and simple dosing through a blood sample [38].…”
Section: Markers For Detection Of Secondary Infectionsmentioning
confidence: 99%
“…Its serum levels are directly associated with the severity of COVID-19 and worse clinical outcome. Patients with elevated CRP levels at the time of admission were associated with a higher risk of disease severity and of developing secondary pulmonary infections [31,38,41,43]. Several studies have demonstrated the correlation between CAP severity and PCT and CRP.…”
Section: Markers For Detection Of Secondary Infectionsmentioning
confidence: 99%
See 2 more Smart Citations